Understanding Concepts and Student Self Efficacy in Learning Mathematics Numbers - Giwa, Giwa (Lembaga Riset Mutiara Akbar, 2023)
The purpose of developing this mathematics learning evaluation is to understand: (1) the application of learning to students' abilities to understand mathematical concepts, (2) differences in abilities to understand mathematical concepts in terms of students' self-efficacy, (3) interaction between learning and the ability to understand mathematical concepts in terms of self-efficacy. student efficacy. Mathematics is one of the important subjects studied by students. Mathematics is a science that studies numbers, algebra, geometry and statistics. Mathematics is the queen of sciences (Mathematics is the Queen of the Sciences), meaning that mathematics does not depend on other fields of study. (Ruseffendi, 1991: 260). Mathematics has an important role in everyday life, from personal life to professional life. However, not all students like mathematics lessons. In fact, many students feel afraid or anxious when taking mathematics lessons. In addition, there are significant differences in the ability to understand mathematical concepts between groups with different levels of self-efficacy. However, the ability to understand mathematical concepts and students' self-efficacy. These results provide an important contribution in the development of mathematics learning methods that can improve students' understanding of mathematical concepts.